Testing of Software and Communicating Systems 20th IFIP TC 6/WG 6.1 International Conference, TestCom 2008 8th International Workshop, FATES 2008, Tokyo, Japan, June 10-13, 2008 Proceedings - Suzuki, Kenji; Higashino, Teruo; Ulrich, Andreas; Hasegawa, Toru (Computer Communication Networks and Telecommunications, 2008)
This book constitutes the refereed proceedings of the 20th IFIP TC 6/WG 6.1 International Conference on Testing Communicating Systems, TestCom 2008, and the 8th International Workshop on Formal Approaches to Testing of Software, FATES 2008, jointly held in Tokyo, Japan, in June 2008. The 18 revised full papers presented together with 2 invited talks were carefully reviewed and selected from initially 58 submissions to both events. The papers cover new approaches, concepts, theories, methodologies, tools, and experiences in the field of testing of communicating systems and general software. They are organized in topical sections on general software testing, testing continuous and real-time systems, network testing, test generation, concurrent system testing, and applications of testing.